CMOS‐Technology‐Enabled Flexible and Stretchable Electronics for Internet of Everything Applications. Issue 22 (26th November 2015) - Hussain, Aftab M.; Hussain, Muhammad M.
Abstract : Flexible and stretchable electronics can dramatically enhance the application of electronics for the emerging Internet of Everything applications where people, processes, data and devices will be integrated and connected, to augment quality of life. Using naturally flexible and stretchable polymeric substrates in combination with emerging organic and molecular materials, nanowires, nanoribbons, nanotubes, and 2D atomic crystal structured materials, significant progress has been made in the general area of such electronics. However, high volume manufacturing, reliability and performance per cost remain elusive goals for wide commercialization of these electronics. On the other hand, highly sophisticated but extremely reliable, batch‐fabrication‐capable and mature complementary metal oxide semiconductor (CMOS)‐based technology has facilitated tremendous growth of today's digital world using thin‐film‐based electronics; in particular, bulk monocrystalline silicon (100) which is used in most of the electronics existing today. However, one fundamental challenge is that state‐of‐the‐art CMOS electronics are physically rigid and brittle. Therefore, in this work, how CMOS‐technology‐enabled flexible and stretchable electronics can be developed is discussed, with particular focus on bulk monocrystalline silicon (100). A comprehensive information base to realistically devise an integration strategy by rational design of materials, devices and processes for Internet of Everything electronics is offered. Abstract : Complementary metal oxide semiconductor (CMOS) technology can enable advanced multifunctional, flexible and stretchable electronics to expand the horizon of electronic applications. Bulk monocrystalline silicon (100) as a substrate for developing such electronics with high performance, energy efficiency, ultra‐large‐scale‐integration (ULSI) density, and performance per cost advantage is reviewed.